Effects of environmental factors on seed germination and seedling emergence of common teasel (dipsacus fullonum) - Huarte, Héctor Roberto (2016)
Fil: Huarte, Héctor Roberto. Universidad Nacional de Lomas de Zamora. Facultad de Ingeniería y Ciencias Agrarias; Argentina